Conceptual Analysis of Human Resource Management Practice in Bangladesh: Current and Future Challenges. (Global Journal of Management and Business Research, 2023)
Abstract- This paper presents a conceptual analysis of Human Resource Management HRM practices in Bangladesh focusing on the current challenges faced by organizations and potential future challenges HRM plays a vital role in managing human capital and ensuring organizational success In the context of Bangladesh a developing country with a growing economy understanding the unique challenges and opportunities faced by HRM practices is crucial The current challenges facing HRM in Bangladesh are discussed in detail These challenges encompass issues such as talent acquisition and retention skill gaps employee engagement diversity and inclusion and compliance with labor laws The analysis explores the impact of these challenges on organizational performance and highlights potential strategies to address them effectively
Keywords: HRM practices; challenges; talent management; employee engagement; diversity